1998
DOI: 10.1046/j.1471-4159.1998.70031167.x
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbate‐Induced Oxidative Inactivation of Zn2+‐Glycerophosphocholine Cholinephosphodiesterase

Abstract: Zn2-glycerophosphocholine cholinephosphodiesterase, responsible for the conversion of glycerophosphocholine into glycerol and phosphocholine, was inactivated during incubation with ascorbic acid at 38°C. The inclusion of copper ions or Fe2~accelerated the ascorbateinduced inactivation, with Cu2~or Cubeing much more effective than Fe2~, suggestive of ascorbate-mediated oxidation. Dehydroascorbic acid had no effect on the phosphodiesterase, but H 202 inactivated the enzyme in a concentration-dependent manner. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 14 publications
(31 reference statements)
0
8
0
Order By: Relevance
“…Glycerophospholipid Metabolism-The inhibitory effect of AA on GlyPhCh choline phosphodiesterase, an enzyme that converts GlyPhCh into glycerol and phosphocholine, has been explored previously in vitro (40). A recent study of AA deficiency in the Gulo Ϫ/Ϫ mice revealed differentiating levels of the downstream products of GlyPhCh choline phosphodiesterase, glycerol, phosphocholine, and choline (41).…”
Section: Journal Of Biological Chemistry 3837mentioning
confidence: 99%
“…Glycerophospholipid Metabolism-The inhibitory effect of AA on GlyPhCh choline phosphodiesterase, an enzyme that converts GlyPhCh into glycerol and phosphocholine, has been explored previously in vitro (40). A recent study of AA deficiency in the Gulo Ϫ/Ϫ mice revealed differentiating levels of the downstream products of GlyPhCh choline phosphodiesterase, glycerol, phosphocholine, and choline (41).…”
Section: Journal Of Biological Chemistry 3837mentioning
confidence: 99%
“…The introduction of hypolipidaemic drugs or their metabolites significantly enhanced the ability of PON1 to reduce the level of cholesterylester hydroperoxides in oxidized LDL [28]. Another strategy to protect enzymes from the inactivation by ROS or lipid peroxidation products would be the employment of substrates, inhibitors or regulators [29,30]. However, an earlier study indicated that the inhibitors of PON1 might be inappropriate for this purpose as demonstrated from the negative role of PON1 inhibitors, such as PD65950, in preventing LDL oxidation [31].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, GPC phosphocholine phosphodiesterase is very susceptible to Cu 2? /ascorbate inactivation [28], but lysoPLC is not. Besides, GPC phosphocholine phosphodiesterase possesses a molecular weight of 74 kDa [12], whereas that of lysoPLC is 65 kDa.…”
Section: Discussionmentioning
confidence: 92%
“…Actually, the procedures for the isolation and purification of brain lysoPLC are similar to those which had been used for the preparation for the purified alkaline phosphatase [4,27]. Therefore, it is supposed that brain lysoPLC may be one of enzymes, located on the external site of cell membrane, such as alkaline phosphatase [4,5], 5 0 -nucleotidase, phosphodiesterase and lysophospholipases [28]. Actually, lysoPLC activity comigrated with alkaline phosphatase activity in Concanavalin A sepharose 4B chromatography, indicating that lysoPLC corresponds to a glycoprotein.…”
Section: Discussionmentioning
confidence: 99%